Aging With Purpose: Systematic Search and Review of Literature Pertaining to Older Adults and Purpose. (December 2017) - Irving, Justine; Davis, Sandra; Collier, Aileen
Purpose can provide a sense of intentionality, guide behavior to achieve personal aims and living objectives, and may offer insight into how and why certain people remain healthy over time. A review of the literature sought to identify contemporary research pertaining to purpose and older adults. Thirty-one studies were selected for evaluation based on inclusion criteria. Research outcomes suggest that greater reported purpose is related to a range of better health and well-being outcomes for older adults. With few exceptions, the literature demonstrates that purpose declines with age. Nevertheless, the potential to experience purpose persists across the life span, by providing opportunities for older adults to continue contributing roles, participate in meaningful activities, and sustain their social value and sense of relevance. Further research could explore how purpose is experienced by the oldest-old age-group, those living within noncommunity settings, and people with age-related cognitive impairment such as dementia.